2018
DOI: 10.1556/1646.10.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

ST-segment depression in left precordial leads in electrocardiogram of patients with acute inferior myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: BackgroundThe early identification of patients with acute inferior ST-segment elevation myocardial infarction (STEMI) with high risk features is particularly important. Acute inferior STEMI may be associated with ST-segment depression in the left precordial leads (V4–V6). This study assessed prognostic value of ST-segment depression in these left precordial leads during the admission of patients with acute inferior STEMI treated with primary percutaneous coronary intervention.MethodsThis retrospective study en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…12 However, Namdar and colleagues found higher prevalence of DM and HTN though there was no significant difference in prevalence of smoking, hyperlipidemia and family history of coronary artery disease in between the groups. 3 Our finding of absence of significant difference in LVEF in between the group was in consistence with the findings of EL Atroush and colleagues. 11 Most of our findings were thus in consistence with several of the reported studies done previously in other settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…12 However, Namdar and colleagues found higher prevalence of DM and HTN though there was no significant difference in prevalence of smoking, hyperlipidemia and family history of coronary artery disease in between the groups. 3 Our finding of absence of significant difference in LVEF in between the group was in consistence with the findings of EL Atroush and colleagues. 11 Most of our findings were thus in consistence with several of the reported studies done previously in other settings.…”
Section: Discussionsupporting
confidence: 92%
“…Variations exists on the angiographic significance as well as on the prevalence of traditional risk factors of those with anterior ST depression in acute inferior STEMI in previous studies done in various settings. 2,3 Some studies have shown that presence of anterior ST depression can be more symptomatic, can have higher severity of the disease and increased mortality but others reported almost similar prognosis. 4,5,6 Since ECG is a very important and readily available tool for diagnosis of MI, understanding the significance of ST depression in anterior leads in inferior MI with reference to coronary angiogram (CAG) would help in better understanding of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The link between RSTD and clinical outcomes has been extensively studied since long , and majority of the previous research suggests that RSTD is associated with clinical prognosis. [9][10][11][12][13][14] ST segment depression occurs in some patients due to multivessel lesions, and the prognosis of these patients is poor. However, even in patients without multivessel disease, RSTD may be associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, the presence of extensive ST-segment depression is usually attributed to severe endocardial ischemia caused by severe multiple vessel damage or left main coronary artery disease (31). Patients with ST-segment depression in the precordial region might exhibit a higher rate of in-hospital mortality (32). In group B, more than 54% of the cases showed significant ST-T changes, and the 3 participant deaths all occurred in group B.…”
Section: Discussionmentioning
confidence: 99%